2014
DOI: 10.1017/s0022215114000577
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative overnight pulse oximetry to predict high dependency unit intervention in children undergoing adenotonsillectomy for obstructive sleep apnoea

Abstract: Background: Post-operative high dependency unit beds are often requested for patients undergoing adenotonsillectomy for obstructive sleep apnoea. This study evaluated the utilisation of high dependency unit beds for such cases at our institution, a paediatric tertiary referral centre. Method: A retrospective case note review of patients admitted to the high dependency unit following adenotonsillar surgery for obstructive sleep apnoea, over a two-year period, was performed. Results: Sixty-six cases were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…The paper by Sharma et al 8 . on trends in assessment and management fits in well with recent papers by Lightbody et al 9 . on pre-operative overnight oximetry as a predictor of high dependency unit requirements and the multicentre study of the T14 outcome measure in paediatric patients by Hopkins et al 10 …”
supporting
confidence: 69%
“…The paper by Sharma et al 8 . on trends in assessment and management fits in well with recent papers by Lightbody et al 9 . on pre-operative overnight oximetry as a predictor of high dependency unit requirements and the multicentre study of the T14 outcome measure in paediatric patients by Hopkins et al 10 …”
supporting
confidence: 69%
“…In conclusion, our study has shown that removal of periods of wakefulness at the start and end of a recording does not affect the oximetry result in the context of testing for suspected OSA, especially if the result is being assessed mainly for dips below 90% as for the McGill score . If oximetry testing is used to reduce the waiting list for polysomnography and to help otorhinolaryngology services prioritise and plan adenotonsillectomy, large numbers of tests need to be performed, and simplicity and accuracy maintained. Removal of awake data manually from oximetry recording introduces an additional time factor and potential for user error.…”
Section: Discussionmentioning
confidence: 81%
“…Overnight oximetry has a very high positive predictive value for the presence of obstructive sleep apnea (OSA) in otherwise healthy children with a good history of airway obstruction during sleep . In the face of increasing demand for polysomnography to diagnose OSA and the limited availability of this test in many settings, many sleep units are using overnight oximetry to reduce the waiting list for polysomnography and to help otorhinolaryngology services prioritise and plan adenotonsillectomy . Determination of an abnormal oximetry for this purpose is based on the frequency of dips in arterial oxygen saturation (SpO 2 ) below the thresholds of 90%, 85%, and 80%, as described in the McGill Oximetry Score .…”
Section: Introductionmentioning
confidence: 99%